Associations Between Work Characteristics, Engaged Well-Being at Work, and Job Attitudes - Findings from a Longitudinal German Study - Luisa L. Brokmeier; Catherin Bosle; Joachim E. Fischer; Raphael M. Herr (Elsevier, 2022)
Objective: The Job Demand & Resources model suggests work characteristics are related to mental well-being and work engagement. Previous work describes the development of a combined construct 'engaged well-being at work' (EWB). To what extent changes in measures of this construct are responsive to changes in job demands and resources or associated with changes in job-related attitudes has not been established. Methods: Longitudinal employee-level data from three waves (German Linked Personnel Panel) were used. Logistic and linear fixed effects regression analyses explored longitudinal associations between changes in EWB for participants over a three-year period with changes in job demands and resources and job-related attitudes (job commitment, satisfaction, and turnover intentions). Results: While job resources were associated with increased odds for a change into a healthier and/or more engaged category of EWB, job demands reduced them. Job resources were more strongly related to higher EWB (ORrange = 1.22 - 1.61) than job demands (ORrange = 0.79 - 0.96). Especially psychological job demands showed negative associations with improved EWB (OR = 0.79). A change from the least desirable category 'disengaged strain' to any other category of EWB was associated with greater odds by up to 20.6 % for increased commitment and job satisfaction and lower odds for turnover intentions. Discussion: Improving work characteristics, especially job resources, could increase employees' EWB, emphasizing the importance of job characteristics for a healthy workplace. Because EWB seems to be associated with job attitudes, an improvement of this indicator would be relevant for employees and employers.